Alleviating Anxiety, Boosting Confidence: A Proposed Model of Willis’ Task-based Learning - Adaninggar Septi Subekti (Yayasan Visi Intan Permata, 2020)
Sufficient attention to the second language (L2) learners' individual differences (IDs) should be given in instructional design as IDs affect differing results of individual learner’s ultimate L2 achievement. To that, this paper presents an example of a lesson plan developed using Willis’ Task-based Learning (TBL). Willis’ TBL framework is selected as it is argued that the framework offers more advantages than Presentation-Practice-Production (PPP) does in terms of the communicative goals and accommodating learners’ affect. The lesson plan is informed by the findings and pedagogical implications of numerous studies on IDs suggesting that L2 instruction should be best designed to accommodate learners’ IDs, for example, but not limited to, minimising learners’ anxiety and boosting their confidence in speaking, through providing a psychologically safe environment stimulating learners’ risk-taking behaviours in L2 learning. Rationales of each stage in the lesson plan are provided to better illustrate how the lesson plan is manifested in the classroom concerning learners' ego and feeling.